Implementasi Investasi Swasta Dan Pengeluaran Pemerintah Terhadap Tingkat Kemiskinan Di Luwu Raya: Implementation of Private Investment and Government Expenditure on Poverty Level in Luwu Raya - Wahida, Vitha; Maming, Rian; Patra, I Ketut (Efektor, 2023)
The purpose of this research is to identify and assess the role of private investment and public spending on the poverty rate in 2014-2021. The population used in this study, namely Luwu Raya Regency in South Sulawesi Province, was used as a sample. The data used in this study is secondary data provided as supporting information. The sampling method of this study uses several linear regression analysis methods, namely classical assumptions and time series data. The results of this study indicate that the independent variables of private investment and public spending do not simultaneously influence the dependent variable on the level of poverty in Luwu Raya. Keywords: Private Investment, Government Spending, Poverty Rate